2007
DOI: 10.1097/inf.0b013e3180684310
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of and Risk Factors for Acinetobacter Species Bloodstream Infection in Children

Abstract: Acinetobacter spp. are an underreported cause of endemic BSI in children. Patients with Acinetobacter spp. BSI are more likely to develop their infection in the home setting compared with patients with BSI caused by other Gram-negative rods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…New research has shown that in children, the pattern is different e for children, infection is significantly more likely to be developed in the home, and by patients who are male. That is, consistent with my augmented hypothesis, under the gendered supervision of parents in home settings, more boys than girls are exposed to this bacteria (Segal et al, 2007).…”
Section: Women Auto-immune Disorders and Depressionsupporting
confidence: 75%
See 1 more Smart Citation
“…New research has shown that in children, the pattern is different e for children, infection is significantly more likely to be developed in the home, and by patients who are male. That is, consistent with my augmented hypothesis, under the gendered supervision of parents in home settings, more boys than girls are exposed to this bacteria (Segal et al, 2007).…”
Section: Women Auto-immune Disorders and Depressionsupporting
confidence: 75%
“…Studies of children with bloodstream infection (BSI) from Acinobacter species, show similar results (Segal, Zaoutis, Kagen, Shah, & Samir, 2007). For adults in the industrialized North and West, exposure to Acinobacteria is generally associated with a hospital stay.…”
Section: Women Auto-immune Disorders and Depressionsupporting
confidence: 57%
“…In the pediatric population, most of the published literature on A. baumannii infections are single-centered, cohort studies and report that risk factors include solid malignancy, renal disease, and male gender 52 . Though patients with A. baumannii infections are commonly hospitalized, infections may develop in the outpatient setting in children with central lines or receiving at home ventilator care 52 .…”
Section: The Clinical Impact Of Antibiotic Resistance In Gnb By Orgamentioning
confidence: 99%
“…Children are virtually absent from the literature on community-onset Acinetobacter infections. One study identified a subset of children with infection onset in the community, but 96% of these had indwelling central venous catheters [9], a clear HCA risk factor, which was not present in the children described here.…”
Section: Discussionmentioning
confidence: 99%